Republic of Lithuania : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Lithuania. (IMF Staff Country Reports; Country Report ;, 2008)
In this report, economic performance of Lithuania over the past decade is discussed. These reflect on EU accession, rapid financial integration, and generally sound macroeconomic policies. Concerns about the rise in external and internal imbalances, characterized by an unsustainable current account deficit, and an increase in domestic inflationary prices, resulting from excess domestic demand are outlined. The findings of the Financial Assessment Stability Program (FASP) are welcome. The Bank of Lithuania's measures in recent years to strengthen banks' capital bases and encourage strong risk management are encouraged.